Ammonium-N nutrition, with and without N-Serve: its effects on the growth of corn roots - Silva, Filomena L. I. M. da; Rossiello, Roberto O. P.; Fernandes, Manlio S. (Pesquisa Agropecuaria Brasileira, 2014)
Under greenhouse conditions, an experiment was made to study the effects of ammonium- N (NH4) 2SO4 with and without the nitrification inhibitor N-Serve on the growth patterns of corn roots. Corn plants were grown for 58 days on pots containing a Brunizem soil material. NH4-N was applied at 13, 28 and 43 days after sowing at 30 µg/g rate. At each of the three dates, plants were harvested and its root fresh and dry weigth, volume, total length and CEC determined. Surface area and average root radius were calculated. Root growth characteristics, throughout the experimental period, were closely related to an exponential model. Regression coefficients were used to calculate relative growth rates of roots. There was a general trend for N-serve to depress the relative growth rate of roots, markedly, total length and surface area. Relative growth rates (R) calculated on dry and fresh weight basis were reduced 20% by N-Serve. These differences were more pronounced at the 43 and 58 days after planting. N-Serve seemed to affect the water relations of the plants. CEC was not affected by the nitrification inhibitor, and decreased only slightly with age.